Global trends in the area of reference materials and the concept of the development of state service of reference materials (Part I) - E. V. Osintseva; S. V. Medvedevskikh; O. N. Kremleva; V. V. Studenok; O. V. Anfilatova; N. S. Baratova (Стандартные образцы)
The article presents the results of research of global trends in the area of reference materials in the following directions: creation of normative documents on RMs, development of RMs, determination of RM metrological characteristics, recognition, approval and use of RMs, informational support of RMs, used in different areas.